Bergson's Philosophy of Biology : Virtuality, Tendency and Time. - Posteraro, Tano (Edinburgh University Press, 2022)
Reconstructs Bergson's philosophy of biology in dialogue with the life sciences of today.
Description based upon print version of record.
Keywords: Bergson, Henri, -- 1859-1941; Biology -- Philosophy.; Biologie -- Philosophie.; PHILOSOPHY / Metaphysics; Biology -- Philosophy